Clinicopathological features and prognosis of idiopathic membranous nephropathy with thyroid dysfunction - Wang, Peiheng; Wang, Shulei; Huang, Bo; Liu, Yiming; Liu, Yingchun; Chen, Huiming; Zhang, Junjun (Frontiers in Endocrinology, 2023)
Background: Thyroid dysfunction is common in patients with kidney disease. However, the relationship between thyroid dysfunction and idiopathic membranous nephropathy (IMN) remains unclear. This retrospective study aimed to investigate the clinicopathological characteristics and prognosis of patients with IMN and thyroid dysfunction compared to patients with IMN and without thyroid dysfunction. Methods: A total of 1052 patients with IMN diagnosed by renal biopsy were enrolled in this study, including 736 (70%) with normal thyroid function and 316 (30%) with abnormal thyroid function. We analyzed the clinicopathological features and prognostic data between the two groups, using propensity score matching (PSM) to reduce the bias. Logistic regression analysis was performed to investigate the risk factors for IMN combined with thyroid dysfunction. Kaplan-Meier curves and Cox regression analysis were used to evaluate the association between thyroid dysfunction and IMN. Results: Patients with IMN and thyroid dysfunction exhibited more severe clinical features. Female sex, lower albumin level, higher D-dimer level, severe proteinuria, and decreased estimated glomerular filtration rate were predictors of thyroid dysfunction in patients with IMN. After PSM, 282 pairs were successfully matched. Results from the Kaplan-Meier curves indicated that the thyroid dysfunction group had a lower complete remission rate (P = 0.044), higher relapse rate (P < 0.001), and lower renal survival rate (P = 0.004). The multivariate Cox regression analysis revealed that thyroid dysfunction was an independent risk factor for complete remission [hazard ratio (HR) = 0.810, P = 0.045], relapse (HR = 1.721, P = 0.001), and composite endpoint event (HR = 2.113, P = 0.014) in IMN. Conclusions: Thyroid dysfunction is relatively common in patients with IMN, and the clinical indicators are more severe in these patients. Thyroid dysfunction is an independent risk factor for poor prognosis in patients with IMN. More attention should be paid to thyroid function in patients with IMN.